Improving Undergraduate Science Education Students’ Research Skills through STEM Learning Integrated with the Research Skill Development (RSD) Framework: A Quasi-Experimental Study - Eli Trisnowati; Wiyanto; Bambang Subali; Sulhadi (Yayasan Nurul Yakin Bunga Tanjung, 2026)
Research skills are an important competency in higher education, but various findings indicate that these skills are still developing unevenly among students. This study aims to examine the relationship between STEM-based science learning integrated with the Research Skill Development (RSD) framework and students' research skill achievement compared to conventional learning. The study used a quantitative approach with a quasi-experimental pretest–posttest control-group design involving 120 third-semester students in the science education study program at a university, who were divided into two experimental and two control classes. The experimental group received STEM learning structured according to the RSD stages and supported by a structured assessment rubric. In contrast, the control group followed the usual lecture-and-assignment-based learning practices. Data were collected using a research skills test developed in line with the RSD framework, then analyzed descriptively and inferentially using the Mann–Whitney U test. The pretest results showed no significant difference between the two groups (p = 0.445). In contrast, significant differences were found in posttest 1 (p = 0.030), posttest 2 (p = 0.010), and posttest 3 (p = 0.011), with the experimental group's average score increasing from 39.7 to 59.1 and the control group's from 37.1 to 54.7. These findings suggest a short-term performance advantage associated with STEM–RSD implementation, depending on the cohort and the instrument used.